Explaining the Slow Pace of Energy Technological Innovation: Why Market Conditions Matter? - Wei Jin; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2014)
As a useful complement to numerous innovation policy studies from a normative perspective, this paper provides a positive framework to analyze the basic economic mechanism of energy technological innovation and explains its slow pace of technological progress. We find that the capital-intensiveness of energy technology is an inhibiting factor to catalyze market size effect and slows innovations and diffusions of energy technology in the market. We also show that the substantial homogeneity of energy products leads to both a monopolistic market structure on the supply side and a weak level of positive pecuniary externality on the demand side, both dampening the incentive of innovation. On the basis of our economic analysis, we recommend that a package of policy responses to accelerating energy innovation should include 1) downsizing heavy assets of energy technologies; 2) deregulating monopolistic energy-supplying markets; and 3) differentiating the homogenous energy products.
Keywords: Q55; Q58; Q43; Q48; O31; 330; The Economics of Technological Innovation; Market Size Effect; Love-for-variety effect; Energy Technology; IT Technology